Determination of heavy metal content of processed fruit products from Tehran's market using ICP- OES: A risk assessment study. (May 2018) - Fathabad, Ayub Ebadi; Shariatifar, Nabi; Moazzen, Mojtaba; Nazmara, Shahrokh; Fakhri, Yadolah; Alimohammadi, Mahmood; Azari, Ali; Mousavi Khaneghah, Amin
Abstract: In this study, the levels of Cd, Hg, Sn, Al, Pb and As of 72 samples (36 samples for fruits juices and 36 samples for fruits canned) of three different brands including of Peach, Orange, Cherry, and Pineapple (18 samples of each fruits) marketed in Tehran, Iran (2015) were evaluated using Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) technique. Also, Probabilistic risk assessment (non-carcinogenic and carcinogenic risks) was estimated by models include target hazard quotient (THQ) and cancer risk (CR) in the Monte Carlo Simulation (MCS) model. However, all samples were contaminated with the heavy metals investigated, most of them not surpassed established standards. The range of concentration for Al, Sn, As, Cd, Hg, and Pb as average in fruit juices were reported as 340.62 (65.17–1039.2), 72.33 (49.76–119.4), 3.76 (1.137–18.36), 2.12 (0.89–3.44), 0.351 and 40.86 (27.87–66.1) μg/kg, respectively. The level of heavy metals measured in different kinds of fruit juices was ranked as Al > Sn > Pb > As > Cd > Hg, and for fruits canned this rank was Pb > Al > Sn > As > Cd > Hg. The range of concentration for Al, Sn, As, Cd, Hg, and Pb in fruits canned were reported as 361.23 (43.15–1121.2), 101.42 (71.45–141.61), 3.92 (1.279–19.50), 2.78 (1.09–5.56), 0.35 and 690.54 (470.56–910.14) μg/kg, respectively. The lead (Pb) concentration in 97.22% (35 out of 36 samples) of fruit juices samples surpassed Codex limit (0.05 mg/kg) and in all samples of FC was lower than the legal limit of Codex limit (1 mg/kg). All of the samples had Tin (Sn) lower than the legal limit of Codex (fruit juices 100 mg/kg and FC 250 mg/kg). The MCS indicated that the rank order of heavy metals in both adults and children based on THQ was Al > Sn > As > Pb > Cd > Hg. The THQ of Al and Sn in the FJ and FC, for both adults, and children, was considerably higher than 1 value. Also, CR of As in both adults and children were higher than 1E-6 value. Although the mean concentration of heavy metal in the FJ and FC was lower than the standard limit, the MCS indicated that adults and children are at considerable non-carcinogenic and carcinogenic risks. Graphical abstract: Highlights: The concentration of Cd, Hg, Sn, Al, Pb and As in fruit juices and fruits canned marketed were measured in Tehran, using ICP-OES technique. The rank order of heavy metals based on concentration was Al > Sn > Pb > As > Cd > Hg. The rank order of heavy metals in both adults and children based on THQ was Al > Sn > As > Pb > Cd > Hg. The THQ of Al and Sn in both adults and children was considerably higher than 1 value. Adults and children were at considerable non-carcinogenic and carcinogenic risk.